Rock-like material manufacturing method considering prefabricated fractures

Through dual source dual energy CT scanning and 3D printing technology, combined with high temperature resistant epoxy phenolic resin, the shortcomings in simulating the complex structure and mechanical behavior of dry hot rocks in the existing technology are solved, and efficient production and performance improvement of rock-like materials are achieved.

CN119715084AInactive Publication Date: 2025-03-28JIANGXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202510228871.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively simulate the complex structure and mechanical behavior of dry hot rocks, especially in terms of fissure structure and permeability.

Method used

The three-dimensional internal structure of the rock sample is obtained through dual source dual energy CT scanning technology, combined with 3D printing technology to generate a crack model that conforms to the actual crack characteristics, and use high-temperature resistant epoxy phenolic resin as the binder to form a rock-like material with similar mineral composition and crack characteristics.

Benefits of technology

Accurate control of natural and artificial cracks is achieved, the temperature resistance of the material is improved, the high similarity between mineral composition and crack distribution is ensured, the permeability and mechanical properties are improved, and it is suitable for geological mechanics experiments and fracturing optimization designs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715084A_ABST
    Figure CN119715084A_ABST
Patent Text Reader

Abstract

The invention provides a manufacturing method of a rock-like material considering prefabricated fractures, and the method comprises the following steps: obtaining three-dimensional scanning data of a rock sample through a double-source double-energy CT scanning system, carrying out three-dimensional reconstruction and analysis on the three-dimensional scanning data, and extracting the particle size distribution range, volume fraction and fracture parameters of minerals in rock; according to the particle size distribution and proportion of minerals, mineral particles consistent with rock minerals in type are prepared through crushing and mixed in proportion, and the stacking porosity is calculated; adding epoxy phenolic resin according to the porosity to form a uniformly mixed material; a fracture structure model is generated through the 3D printing technology, and camphor is selected as a fracture model consumable; fully stirring the crack model and the mixed material, filling the mold in a layered manner, and compacting; heating in a muffle furnace to cure the epoxy phenolic resin, sublimating through camphor to form a crack structure, and cooling to obtain the rock-like material with similar mineral composition and crack characteristics. According to the method, the rock similar material containing the prefabricated cracks can be rapidly manufactured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of rock-like material manufacturing, and in particular to a method for manufacturing rock-like materials taking prefabricated cracks into consideration. Background Art

[0002] Hot dry rock is a thermal energy resource in deep high-temperature rock mass with high temperature and high pressure characteristics. Its complex geomechanical properties and high temperature environment make direct research difficult. Similar materials can simulate the mineral composition, fracture characteristics and mechanical behavior of hot dry rock under laboratory conditions, which is helpful to explore the laws of fracture expansion and optimize fracturing design.

[0003] Existing methods for making rock-like materials with prefabricated fractures include inserting prefabricated fracture molds, mold forming, 3D printing, cutting, and chemical etching. These methods have the following problems: inserting fracture molds and mold forming methods are difficult to flexibly adjust fracture parameters, and complex fracture networks are difficult to simulate; 3D printing is costly and inefficient, and fracture permeability is difficult to truly reflect; cutting methods may damage the sample and cannot produce complex internal fractures; chemical etching methods have large randomness and poor uniformity of fractures.

[0004] In addition, traditional similar materials (such as cement, gypsum, etc.) have insufficient temperature resistance, their mechanical properties are far from those of hot dry rocks, their ability to simulate mineral components is limited, and their fracture structure and permeability are difficult to meet actual needs. These problems limit the application of existing similar materials in hot dry rock research. Summary of the invention

[0005] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0006] To this end, the first objective of the present application is to propose a method for producing rock-like materials taking into account prefabricated fractures.

[0007] To achieve the above-mentioned purpose, the first embodiment of the present application proposes a method for manufacturing a rock-like material taking into account prefabricated cracks, comprising: The rock sample is placed in a dual-source dual-energy CT scanning system for scanning to obtain three-dimensional scanning data of the rock sample; Performing three-dimensional reconstruction and analysis on the three-dimensional scanning data to obtain the particle size distribution range and volume fraction of the minerals inside the rock, as well as the volume fraction, pore diameter, aspect ratio and fractal dimension of pores and cracks; Prepare mineral particles consistent with the mineral type inside the rock, crush the mineral particles of the same type into different particle size ranges according to the particle size distribution range and proportion of different minerals inside the rock, and calculate their stacking porosity after mixing; According to the stacking porosity of the mixed mineral particles, a high temperature resistant epoxy phenolic resin is calculated and added as a binder to form a uniform mixed material; The 3D printing technology was used to establish a fracture structure model that conforms to the real fracture structure distribution characteristics of hot dry rock, and camphor was selected as the consumable material for 3D printing fracture structure; The fracture structure model and the mixed material are placed in a container with a Teflon coating and stirred to mix evenly, the stirred materials are loaded into a mold, filled in layers and compacted, and the pressure is maintained until the material is initially solidified to generate a dry hot rock-like material; The dry hot rock-like material is placed in a muffle furnace, and the epoxy phenolic resin is accelerated to solidify by heating, and the camphor is sublimated to form a crack structure; After the solidification and crack generation are completed, the hot dry rock-like material is taken out from the muffle furnace and cooled to room temperature to obtain a rock-like material with similar mineral composition and crack characteristics.

[0008] Optionally, the step of placing the rock sample in a dual-source dual-energy CT scanning system for scanning to obtain three-dimensional scanning data of the rock sample includes: The rock sample is placed in a dual-source dual-energy CT scanning system, wherein the system uses two X-ray sources with different energies to scan the rock sample, and the attenuation characteristics of different minerals in the rock under different energy X-rays are calculated by the following formula:

[0009]

[0010] in, and is the intensity of X-rays after penetrating the rock sample, and is the incident X-ray intensity of two different energy sources, and is the linear attenuation coefficient of the material under different energy rays, is the rock thickness; By taking the logarithm of the above formula and solving it in parallel, the linear attenuation coefficient of the mineral is obtained. According to the attenuation characteristics of the mineral, the type and density distribution of the mineral in the rock are determined.

[0011] Optionally, the three-dimensional reconstruction and analysis of the three-dimensional scanning data to obtain the particle size distribution range and volume fraction of the minerals inside the rock, as well as the volume fraction, pore diameter, aspect ratio and fractal dimension of pores and cracks, includes: Reconstruct the three-dimensional scan data using three-dimensional reconstruction software, convert the three-dimensional scan data into a 16-bit grayscale image, and use a threshold segmentation method to obtain the spatial distribution characteristics of minerals inside the rock and the distribution characteristics of natural pores and cracks; Through the software annotation and analysis function, the particle size distribution range and volume fraction of minerals inside the rock are statistically analyzed, and the aperture, aspect ratio and volume fraction of the cracks are analyzed. At the same time, the fractal dimension function is used to calculate the fractal dimension of the cracks.

[0012] Optionally, the step of preparing mineral particles consistent with the mineral type inside the rock, crushing the mineral particles of the same type into different particle size ranges according to the particle size distribution range and proportion of different minerals inside the rock, and calculating the stacking porosity after mixing, comprises: Based on the particle size distribution range and proportion of different minerals in the rock, a crusher is used to crush the mineral particles to reach the required particle size range; According to the particle sizes and volume fractions of different minerals in the rock, crushed mineral particles of different particle size ranges are mixed in proportion; The mixed mineral particles are filled into the mold in layers, compacted using a small vibrator and pressurized step by step to the target pressure, and the volume of the compacted particles is recorded; The stacking porosity is determined by calculating the ratio of the volume of the mixed particles to the total volume after compaction. The calculation formula for the stacking porosity is:

[0013] in, is the stacking porosity, is the volume of mineral particles, is the pore volume between particles.

[0014] Optionally, the step of calculating and adding a high temperature resistant epoxy phenolic resin as a binder according to the stacking porosity of the mixed mineral particles to form a uniform mixed material comprises: The volume fraction of the pores between the particles is calculated by the stacking porosity, and the amount of the required binder is determined according to the density of the epoxy phenolic resin and the volume fraction of the mineral particles; The calculated epoxy phenolic resin is uniformly added to the mixed mineral particles, and it is ensured that it fully fills the pores between the particles to form a uniform mixed material.

[0015] Optionally, the method of using 3D printing technology to establish a fracture structure model that conforms to the distribution characteristics of the real fracture structure of hot dry rock, and selecting camphor as a consumable material for 3D printing the fracture structure, includes: A fracture structure model similar to the rock sample is established by computer modeling software. The model includes aperture, slenderness ratio and fractal dimension parameters. The total volume of the model is determined according to the volume fraction of the rock fractures. The formula is:

[0016] in, is the total volume of the fracture structure model, is the volume fraction of rock pores, is the total volume of rock-like material; The fracture structure model is exported as a mesh file in .stl format, and the model is printed using a 3D printing device using camphor as a consumable.

[0017] Optionally, the fracture structure model and the mixed material are placed in a container with a Teflon coating and stirred to mix evenly, the stirred materials are loaded into a mold, filled in layers and compacted, and the pressure is maintained until the material is initially solidified to generate a dry hot rock-like material, including: Placing the fracture structure model and the mixed mineral particle material together in a container with a Teflon coating on the inner wall, and mixing them by mechanical stirring or manual stirring to ensure that the fracture structure model, the mineral particles and the binder are fully and evenly distributed; The stirred mixed material is loaded into the mold in layers, and each layer of material is compacted using a vibrator to eliminate voids; A small pressure device is selected to pressurize the loaded material step by step. The target pressure is maintained for a period of time during the step-by-step pressurization process to ensure that the material is initially solidified and forms a dense structure. The pressure device is then removed and the mold is dismantled to generate a preliminarily solidified hot dry rock-like material.

[0018] Optionally, the hot dry rock-like material is placed in a muffle furnace, and the epoxy phenolic resin is accelerated to solidify by heating, and the camphor is sublimated to form a crack structure, comprising: The preliminarily solidified hot dry rock-like material is placed in a muffle furnace, and the temperature of the muffle furnace is set to 200° C.; camphor is converted from a solid state to a gaseous state by heating, and a prefabricated crack structure is formed inside the material, and the spatial distribution of the cracks conforms to the crack model characteristics designed in the three-dimensional modeling process; A serpentine condenser is connected to the gas outlet of the muffle furnace, and the gaseous camphor is re-condensed into a solid through a cooling device, thereby realizing the recovery and reuse of the camphor.

[0019] Optionally, also include: Measuring parameters of the rock-like material after cooling, including particle size distribution and volume fraction of minerals, volume fraction of pores and fissures, pore diameter, aspect ratio and fractal dimension, to verify whether it is consistent with the three-dimensional scanning data of the prototype rock sample; Record the manufacturing parameters used in each manufacturing process, including mineral particle grading ratio, binder dosage, fracture model design parameters, heating rate and constant temperature time; By analyzing the relationship between the manufacturing parameters and the final material properties, adjusting the ratio of different components and the manufacturing process, conducting orthogonal experiments, and recording the test results in a computer program, a manufacturing parameter database is formed; Based on the manufacturing parameter database, the corresponding rock-like material proportions and process flows that meet the requirements of different rock characteristics are automatically generated according to the CT scanning parameters of the prototype rock sample.

[0020] The method for manufacturing a rock-like material with prefabricated cracks provided in the present application can effectively solve the deficiencies in the prior art in simulating the complex structure and mechanical behavior of hot dry rocks. The technical solution provided in the embodiments of the present application brings at least the following beneficial effects: Through dual-source dual-energy CT scanning technology, the three-dimensional internal structure of the rock sample is accurately obtained, and combined with 3D printing technology, a fracture model that conforms to the actual fracture characteristics is generated, thereby achieving precise control of natural and artificial fractures; the high-temperature resistant epoxy phenolic resin used as a binder significantly improves the temperature resistance of the material and can adapt to the high temperature requirements of the hot dry rock environment; the mineral particle grading is adjusted and optimized to ensure that the mineral composition is highly similar to the fracture distribution, making up for the shortcomings of traditional similar materials in mineral diversity and mesostructure restoration; the complex fracture network is simulated by camphor sublimation, which solves the difficulties of existing methods in simulating fracture uniformity, connectivity and permeability; in addition, the present application realizes the standardization and efficiency of the production process by optimizing the process and parameter database, and the obtained material is highly similar to hot dry rock in terms of mechanical properties, pore structure and permeability, and can be widely used in geomechanical experiments, fracturing optimization design and seepage characteristics research, thereby improving the experimental accuracy and efficiency of studying hot dry rocks.

[0021] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which: Figure 1 A schematic flow chart of a method for producing a rock-like material taking into account prefabricated fractures provided in an embodiment of the present application; Figure 2 This is a schematic diagram of the pore fracture and mineral three-dimensional reconstruction model of the granite-type hot dry rock provided in the embodiment of the present application. DETAILED DESCRIPTION

[0023] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0024] Hot dry rock is a thermal energy resource hidden in high-temperature rock masses deep in the earth, with a temperature above 150°C. The high-temperature and high-pressure environment and its complex geomechanical properties make direct research on it face many difficulties. Similar materials can simulate some key characteristics of hot dry rocks under laboratory conditions, which is helpful to further explore the thermal-mechanical coupling mechanism and crack expansion law of hot dry rocks. There are various cracks in hot dry rocks themselves. Factors such as the shape, direction, and density of the cracks will affect the artificial fracturing effect and fluid seepage characteristics of hot dry rocks. By studying similar materials of hot dry rocks containing different prefabricated cracks, we can have a deeper understanding of the interaction between natural cracks and artificial cracks, which is conducive to optimizing fracturing design and improving reservoir transformation efficiency.

[0025] The existing methods for making rock-like materials with prefabricated cracks are generally as follows. (1) Inserting a prefabricated crack mold. Before pouring the similar material, insert the crack piece with a good threshold into the specific position and angle of the mold, and then pour it, so that a rock-like material with a threshold crack of a specific width, angle and length can be made. (2) Mold forming method. Directly design a mold with a specific crack shape and size, and then pour the similar material raw material into the mold. It is suitable for making similar materials with complex crack shapes and distributions. (3) 3D printing. Using 3D printing, according to the preset model, only powder is spread on the prefabricated part without dripping the binder, and the similar material with cracks is directly printed. The advantage is that the shape, size, connectivity, etc. of the cracks can be accurately controlled by computer design; (4) Cutting method. First, a complete sample without cracks is made, and then the complete sample is cut by wire cutting or sawing tools to form a rock-like model with prefabricated cracks. (5) Chemical erosion or dissolution method. Special ingredients are added to a complete sample of similar materials, which is then immersed in a special chemical solvent. By controlling parameters such as temperature and concentration of the corrosive solution, a chemical reaction occurs inside the material, forming similar crack channels.

[0026] However, the existing methods for making rock-like materials with prefabricated fractures have the following disadvantages and shortcomings: (1) Inserting a prefabricated fracture mold. The prefabricated fractures formed are relatively simple and difficult to simulate complex fracture networks. The part inserted into the mold may affect the density of the surrounding materials. (2) Mold forming method. The mold cost is high and has poor flexibility. It is difficult to adjust and modify the fracture parameters. Some materials may be difficult to demold and damage the mold. (3) 3D printing. The cost is high and the printing speed is relatively slow. It is not suitable for making large-sized similar material samples. The prefabricated fractures are still filled with powder, but there is no adhesive. It is not suitable for simulating the seepage process in hot dry rocks. (4) Cutting method. The cutting process is prone to other damage to the sample, and it is impossible to produce a complex internal fracture network. (5) Chemical erosion or dissolution method. The erosion or dissolution process is difficult to control, the distribution of the fracture shape and size is relatively random, and the uniformity of the fractures on the surface and inside of the sample is difficult to guarantee.

[0027] In addition, there are some common technical difficulties in simulating hot dry rock materials, especially the difficulty of rock-like materials to truly reflect the microscopic properties of rocks. For example, it is difficult to fully simulate the characteristics of mineral particles, while rocks are composed of a variety of natural minerals with complex components and a certain proportion. Existing rock-like materials are difficult to accurately reproduce the mineral composition of rocks. Even if similar aggregates or fillers are added, the diversity of minerals cannot be reflected. At the same time, traditional similar raw materials, such as cement, gypsum, mortar, etc., still have obvious deficiencies in the production of hot dry rock materials: (1) Insufficient temperature resistance, it is difficult to simulate the temperature environment of hot dry rock. (2) Insufficient physical and mechanical properties. There is a large gap between the mechanical properties of traditional materials and the high density and high strength characteristics of hot dry rock. (3) The pore structure and permeability are very different. Prefabricated cracks are difficult to meet the permeability of original cracks in hot dry rocks.

[0028] In view of the above problems, the present application provides a method for manufacturing a rock-like material taking into account prefabricated cracks. Figure 1 A schematic diagram of a process for producing a rock-like material with prefabricated cracks provided in an embodiment of the present application. Figure 1 As shown, the method comprises the following steps: S1, placing the rock sample in a dual-source dual-energy CT scanning system for scanning to obtain three-dimensional scanning data of the rock sample.

[0029] In the embodiment of the present application, a hot dry rock sample with different crack distribution is first selected. The shape and size of the sample are not clearly specified, and only need to meet the scanning size limit and accuracy requirements of the dual-source dual-energy CT scanning system. Then, the hot dry rock sample is placed on the sample stage of the CT scanning system, and the scanning voltage, current, resolution and other parameters are set and fixed according to the rock size, and the CT scanning system is started to scan the rock to obtain three-dimensional scanning data of the rock sample.

[0030] It should be noted that the CT scanning system used in this application is a specific dual-source dual-energy CT with two X-ray sources of different energies. It can accurately identify the absorption and attenuation characteristics of different minerals inside the rock under X-ray irradiation of different energies, thereby providing basic data support for subsequent fracture simulation.

[0031] Step S1 specifically includes the following steps: S11, placing the rock sample in a dual-source dual-energy CT scanning system, wherein the system uses two X-ray sources with different energies to scan the rock sample.

[0032] It should be noted that different minerals inside the rock show different absorption and attenuation characteristics under the irradiation of X-rays of different energies. The intensities of the two energy rays after penetrating the rock sample satisfy the following linear attenuation formulas:

[0033]

[0034] in, and is the intensity of X-rays after penetrating the rock sample, and is the incident X-ray intensity of two different energy sources, and is the linear attenuation coefficient of the material under different energy rays, is the rock thickness.

[0035] According to the above formula, by analyzing the intensity changes after the two radiation sources penetrate, the absorption and attenuation characteristics of different minerals inside the rock can be determined. The dual-source dual-energy CT scanning system used in this application can fully obtain the microscopic characteristics of the minerals inside the rock sample through the superposition scanning of multiple energy radiation sources, providing high-precision data support for fracture research.

[0036] S12, taking the logarithm of the above formula and solving it in parallel, obtain the linear attenuation coefficient of the mineral, and determine the type and density distribution of the mineral in the rock based on the attenuation characteristics of the mineral.

[0037] In the embodiment of the present application, the following formula is obtained by taking the logarithm of the above linear attenuation formula:

[0038]

[0039] Then, by solving the problem simultaneously, we can calculate the linear attenuation coefficient of the minerals inside the rock at different ray energies. and According to the attenuation coefficient and , combined with the scanning data of the dual-source dual-energy CT system and subsequent data analysis, the type and density distribution of minerals in rock samples can be accurately determined.

[0040] S2, 3D reconstruction and analysis of 3D scanning data to obtain the particle size distribution range and volume fraction of minerals inside the rock, as well as the volume fraction, pore diameter, aspect ratio and fractal dimension of pores and fractures.

[0041] In the embodiment of the present application, the acquired 3D scanning data of the rock sample is 3D reconstructed and analyzed, and the 3D structural model of the rock sample is generated by using reconstruction software to extract the mineral distribution and fracture parameter information inside the rock. The embodiment of the present application can clearly restore the internal characteristics of the rock sample through reconstruction and analysis of the scanning data, providing an important reference for the subsequent design of similar materials.

[0042] Step S2 specifically includes the following steps: S21, reconstruct the 3D scanning data using 3D reconstruction software, convert the 3D scanning data into a 16-bit grayscale image, and use the threshold segmentation method to obtain the spatial distribution characteristics of minerals inside the rock and the distribution characteristics of natural pores and fractures.

[0043] As a possible implementation method, this application uses VoxelStudioRecon software to reconstruct the acquired 3D scanning data to reconstruct the mineral and crack space characteristics inside the rock, and uses Avizo software to perform 3D processing on the reconstructed data, converting the scanning data into a 16-bit grayscale image (grayscale value range is 0-65535). The grayscale image is processed by the threshold segmentation method to obtain the spatial distribution characteristics of the minerals inside the rock and the distribution characteristics of the natural pores and cracks.

[0044] In one embodiment of the present application, the pore fracture and mineral three-dimensional reconstruction model of granite-type hot dry rock is as follows: Figure 2 As shown, the reconstruction Figure 2 The spatial relationship between cracks and mineral particles inside the rock can be clearly shown.

[0045] S22, through the software annotation and analysis function, the particle size distribution range and volume fraction of the minerals inside the rock are statistically analyzed, and the aperture, aspect ratio and volume fraction of the cracks are analyzed. At the same time, the fractal dimension function is used to calculate the fractal dimension of the cracks.

[0046] In the embodiment of the present application, the Label Analysis function in the Avizo software is used to perform a detailed analysis on the three-dimensional rock model after threshold segmentation, and the key parameters of the minerals and cracks inside the rock are counted respectively. Specifically: The Label Analysis function is used to count the particle size and volume percentage of each mineral particle. Statistical methods are used to divide the mineral particle size distribution into multiple intervals, and the volume fraction of mineral particles in each particle size distribution interval is calculated. The corresponding particle size volume percentages are added together to obtain the overall mineral particle size distribution range and volume fraction characteristics.

[0047] In addition, statistical analysis is performed on the pore and fracture 3D model after threshold segmentation to obtain parameters such as the aperture, slenderness ratio, and volume fraction of each fracture. At the same time, the fractal dimension of the fracture 3D model is calculated using the Fractal Dimension function in Avizo to fully characterize the complexity and spatial distribution characteristics of the fractures.

[0048] Through the three-dimensional reconstruction and analysis of the embodiments of the present application, the particle size distribution range and volume fraction of the minerals inside the rock, as well as the volume fraction, pore size, aspect ratio and fractal dimension of the cracks can be accurately quantified. These data not only provide a scientific basis for the study of the expansion law of hot dry rock cracks and fluid seepage characteristics, but also can guide the production of similar materials and the precise design of crack structures.

[0049] S3, prepare mineral particles that are consistent with the mineral type inside the rock, crush the same type of mineral particles into different particle size ranges according to the particle size distribution range and proportion of different minerals inside the rock, and calculate their stacking porosity after mixing.

[0050] In the embodiment of the present application, mineral particles matching the type and particle size distribution characteristics of the minerals in the rock sample are prepared, and the stacking porosity of the mineral particles is calculated through crushing, mixing and compaction experiments. The present application ensures that the particle gradation of the final mixture is consistent with the mineral distribution in the rock sample by precisely controlling the gradation and proportion of the mineral particles, laying the foundation for the subsequent production of rock-like materials.

[0051] Step S3 specifically includes the following steps: S31, based on the particle size distribution range and proportion of different minerals in the rock, a crusher is used to crush the mineral particles to reach the required particle size range.

[0052] In the embodiment of the present application, mineral particles consistent with the mineral type inside the rock are prepared, and according to the particle size distribution range and volume fraction data of the mineral inside the rock obtained in step S2, a crusher is used to crush the mineral particles to reach the desired particle size range.

[0053] It is understandable that due to the stacking mode of mineral particles, even if they are completely compacted, there will be stacking porosity. Therefore, the embodiments of the present application use minerals with different particle gradations and particle sizes to minimize the stacking porosity after compaction. The stacking porosity calculation method of the dense state is the ratio of the particle volume to the total volume (including the particle volume and the void volume between the particles), which will be calculated through subsequent design experiments.

[0054] Take a certain rock as an example, it is composed of three minerals, namely mineral A, mineral B and mineral C, and their volume fractions are , and the corresponding density The embodiments of the present application can better match the mineral particle size characteristics inside the rock by crushing the original minerals into different particle size ranges, providing an accurate basis for mixing and grading.

[0055] S32, according to the particle size and volume fraction of different minerals in the rock, the crushed mineral particles of different particle size ranges are mixed in proportion.

[0056] In the embodiment of the present application, the crushed mineral particles are mixed according to the particle size and proportion so that the particle gradation of the mixture is consistent with the distribution of the corresponding minerals in the rock sample. During mixing, the volume fractions of different minerals in the rock in step S2 need to be converted into mass fractions to ensure that the density and composition of the mixture are consistent with the prototype rock. For example, the mixing ratio of three minerals A, B and C is calculated by mass ratio as follows:

[0057] By precisely controlling the mixing ratio, the mineral composition and distribution characteristics of the rock sample can be simulated to the greatest extent.

[0058] S33, the mixed mineral particles are filled into the mold in layers, compacted using a small vibrator, and pressurized step by step to the target pressure, and the volume of the particles after compaction is recorded.

[0059] In the embodiment of the present application, first, the mixed mineral particles are filled into a high-strength mold in layers, and a small vibrator is used to compact the mineral particles to initially compact them to avoid the formation of obvious voids between the particles.

[0060] As a possible implementation, a high-strength cylindrical or rectangular parallelepiped with scales is selected as the high-strength mold of the above embodiment, and the inner wall is required to be smooth in order to reduce the friction between the particles and the wall.

[0061] In addition, the mold should have a removable top cover to facilitate loading.

[0062] In addition, to facilitate the subsequent removal of the mold, the four sides and the bottom of the mold in the embodiment of the present application are designed in an assembled manner to improve the convenience of operation.

[0063] After repeating this process many times until the mold is full, a small pressure device matching the inner diameter of the mold is selected to gradually pressurize the filled mineral particles.

[0064] It should be noted that the initial pressure should not be too high to prevent the original structure of the mineral particles from being destroyed. For example, an initial pressure of 0.5 to 1 MPa can be set, and then the pressure can be slowly increased until the target compaction pressure is reached. The target pressure needs to be estimated and reduced based on the pressure state of the hot dry rock. During the compaction process, the deformation of the particles should be continuously observed to ensure that the particles will not be broken due to excessive pressure. After reaching the target compaction pressure, maintain a steady pressure for a period of time to fully compact the particles. Record the compaction volume of the mineral particles at this time. .

[0065] S34, determine the stacking porosity by calculating the ratio of the volume of the mixed particles to the total volume after compaction.

[0066] In the examples of the present application, the stacking porosity is an important parameter reflecting the compaction state of the particles, and the calculation formula is as follows:

[0067] in, is the stacking porosity, is the volume of mineral particles, is the pore volume between particles.

[0068] Specifically, given the known density and mass of a mineral particle, the particle volume can be calculated , the stacking porosity in the compacted state It can be calculated by the formula to be sure.

[0069] If the volume of the rock-like material mold required is known to be , then the masses of the three mineral particles are: , , .

[0070] Through the above steps, the embodiment of the present application not only achieves accurate grading of mineral particles, but also can effectively reduce the stacking porosity of the particles after compaction, thereby providing a reliable particle basis for subsequent production of similar materials.

[0071] S4, according to the stacking porosity of the mixed mineral particles, high temperature resistant epoxy phenolic resin is calculated and added as a binder to form a uniform mixed material.

[0072] In the embodiment of the present application, the gaps between the mixed mineral particles are ensured to be fully filled and combined, and the heat resistance and mechanical properties of the material in a high temperature environment are ensured, and a high temperature resistant epoxy phenolic resin is used as a binder. Epoxy phenolic resin has the advantages of both epoxy resin and phenolic resin, has excellent heat resistance and mechanical strength, and can maintain good performance even in a high temperature environment above 300°C, making it an ideal choice for making materials similar to dry hot rocks.

[0073] Step S4 specifically includes the following steps: S41, the volume fraction of the pores between the particles is calculated by stacking porosity, and the amount of the required binder is determined according to the density of the epoxy phenolic resin and the volume fraction of the mineral particles.

[0074] In the embodiment of the present application, according to the stacking porosity of the mixed mineral particles , the volume fraction of the voids between the particles can be calculated to determine the amount of binder required.

[0075] For a known rock-like material mold volume The volume fractions of the three minerals A, B, and C are The stacking porosity is The density of the epoxy phenolic resin used is , then the required mass calculation formula of epoxy phenolic resin binder is:

[0076] In this formula, It represents the volume fraction of the voids between particles, ensuring that the amount of epoxy phenolic resin used is sufficient to fill the pores between particles.

[0077] S42, adding the calculated epoxy phenolic resin evenly into the mixed mineral particles, and ensuring that the epoxy phenolic resin fully fills the pores between the particles to form a uniform mixed material.

[0078] In the embodiment of the present application, the epoxy phenolic resin calculated according to the above formula is added to the mixed mineral particles in proportion, and the mixed mineral particles are fully stirred using a stirring device to ensure that the binder can be evenly distributed and completely fill the gaps between the particles, thereby forming a uniform mixed material. To ensure the mixing effect, a mechanical stirrer can be used for continuous stirring until the binder and the mineral particles are evenly mixed and there are no obvious gaps.

[0079] Through the calculation and uniform mixing processing of the embodiments of the present application, not only can the pores between mineral particles be effectively filled and the density of the mixed material be improved, but also the stability and mechanical properties of rock-like materials in high temperature environments can be ensured, providing a basis for subsequent material molding and simulation of fracture structures.

[0080] S5, using 3D printing technology to establish a fracture structure model that conforms to the real fracture structure distribution characteristics of hot dry rock, and camphor is selected as the consumable material for 3D printing fracture structure.

[0081] In the embodiment of the present application, a fracture structure model similar to that of a hot dry rock sample is established through computer modeling and 3D printing technology. The model can not only accurately reflect the spatial characteristics of hot dry rock fractures (such as aspect ratio, pore size and fractal dimension), but also ensure that the volume fraction of the pores in the hot dry rock is consistent with that in the hot dry rock by controlling the volume of the model. The 3D printing material used is the organic compound camphor, whose characteristics allow it to completely volatilize to form pores during the subsequent heating process, providing key support for the production of rock-like materials with real fracture characteristics.

[0082] Step S5 specifically includes the following steps: S5, a fracture structure model similar to that of the rock specimen is established through computer modeling software.

[0083] In the embodiments of the present application, a series of fracture structure models are established based on the fracture characteristic data (such as pore size, aspect ratio and fractal dimension) of the hot dry rock sample using computer modeling software. In order to ensure that the fracture model is consistent with the actual fracture of the hot dry rock, the total volume of the fracture needs to be controlled to be consistent with the volume fraction of the pores of the hot dry rock in the model design. The calculation formula for the total volume of the model is:

[0084] in, is the total volume of the fracture structure model, is the volume fraction of rock pores, is the total volume of rock-like material.

[0085] In addition, after the model is established, the morphology and connectivity of the cracks need to be further adjusted according to actual needs to ensure that the crack parameters in the model (such as pore size distribution, aspect ratio and fractal dimension) meet the experimental requirements.

[0086] S52, exporting the fracture structure model into a mesh file in .stl format, and completing the model printing by using a 3D printing device with camphor as consumables.

[0087] In the embodiment of the present application, the designed fracture structure model is exported as a surface mesh file in .stl format, and the file is input into a 3D printing device for printing. In the present application, camphor is selected as a consumable material for 3D printing fracture structure. Camphor, as an organic compound, has a low volatilization rate at room temperature, and the volatilization rate is accelerated and there is no residue in a high temperature environment, and it can be completely sublimated to form pores in the subsequent production process. The plasticity and stability of camphor make it very suitable for modeling and molding of hot dry rock fracture structures.

[0088] During the printing process, the printing parameters (such as resolution and layer thickness) need to be adjusted according to the complexity of the fracture model to ensure the accuracy of the model and the connectivity of the fractures. At the same time, since camphor is toxic, necessary protective measures should be taken during the printing process, such as using ventilation equipment to prevent the accumulation of camphor volatiles.

[0089] Through the 3D modeling and printing technology of the embodiment of the present application, high-precision simulation of the fracture structure can be achieved, providing effective support for the subsequent formation of porous fractures in materials similar to hot dry rocks. This method can not only control the morphology, distribution and connectivity of the fractures, but also flexibly adjust the parameters of the fracture model according to experimental requirements, with high flexibility and operability.

[0090] S6, placing the fracture structure model and the mixed material in a container with a Teflon coating and stirring and mixing them evenly, loading the stirred material into a mold, filling and compacting it in layers, and maintaining the pressure until the material is initially solidified to generate a material similar to dry hot rock.

[0091] In the embodiment of the present application, the mineral particles, epoxy phenolic resin binder and the crack structure model made of camphor are mixed, and the preliminarily solidified dry hot rock-like material is generated by layered filling, vibration compaction and pressure molding. This step uses a container and a pad with a Teflon coating, which can effectively reduce the adhesion of the binder to the container or the pressurizing device, avoid the loss of raw materials, and ensure uniform mixing and material density.

[0092] Step S6 specifically comprises the following steps: S61, placing the fracture structure model and the mixed mineral particle material in a container with a Teflon-coated inner wall, and mixing them by mechanical stirring or manual stirring to ensure that the fracture structure model, the mineral particles and the binder are fully and evenly distributed.

[0093] In the examples of the present application, the fracture structure model made of epoxy phenolic resin, mineral particles and camphor is weighed according to the calculated ratio and placed in a container with a Teflon coating on the inner wall. The Teflon coating has extremely low surface energy and good non-stick properties, which can effectively prevent the adhesive from adhering to the inner wall of the container and reduce material waste.

[0094] Furthermore, the fracture structure model, mineral particles and binder are fully mixed by mechanical agitator or manual stirring to ensure that the fracture model is evenly distributed in the mixed material, providing a good uniformity foundation for subsequent material molding. S62, the stirred mixed material is loaded into the mold in layers, and each layer of the material is compacted using a vibrator to eliminate voids.

[0095] In the embodiment of the present application, the uniformly mixed materials are loaded into the mold in layers, and after each layer of material is loaded, a small vibrator is used to vibrate the mold to initially compact the materials and eliminate most of the voids. The vibration treatment can prevent the formation of obvious voids inside the mixed material, and at the same time help to improve the density and overall uniformity of the material.

[0096] S63, select a small pressure device to pressurize the loaded material step by step, maintain the target pressure for a period of time during the step-by-step pressurization process, ensure that the material is initially solidified and forms a dense structure, then remove the pressure device and dismantle the mold to generate a preliminarily solidified hot dry rock-like material.

[0097] In the embodiment of the present application, after the vibrated mixed material is completely filled, a small pressure device is used to pressurize step by step. The initial pressurization pressure is consistent with that in step S3, and is generally set to 0.5 to 1 MPa to prevent the epoxy phenolic resin or mineral particles from being damaged due to excessive pressure. The pressure is then gradually increased until the final target pressure is reached, and the pressure is maintained for a period of time to allow the material to initially solidify and form a dense structure.

[0098] In addition, to prevent the material from sticking to the pressure device during the compaction process, a Teflon-coated pad is installed at the end of the pressure device to reduce the contact between the adhesive and the equipment. After the material is fully solidified, the pressure device is removed and the mold is dismantled to generate a preliminarily solidified dry hot rock-like material, laying the foundation for subsequent crack formation and experimental research.

[0099] S7, placing a material similar to dry hot rock in a muffle furnace, accelerating the curing of epoxy phenolic resin by heating, and causing camphor to sublime to form a crack structure.

[0100] In an embodiment of the present application, a preliminarily solidified hot dry rock-like material is placed in a muffle furnace, and the epoxy phenolic resin is completely cured by controlling the temperature rise process, while accelerating the conversion of camphor from solid to gas, ultimately forming a prefabricated crack structure inside the material, and the spatial distribution of the cracks is consistent with the characteristics of the crack model designed during the three-dimensional modeling process.

[0101] Specifically, the hot dry rock-like material after the mold is removed is placed in a muffle furnace, and the temperature of the muffle furnace is set to 200°C and maintained for a period of time. This temperature setting can effectively accelerate the curing process of epoxy phenolic resin while ensuring that the bonding properties of the material are not affected. Camphor, as a consumable material for the crack structure, sublimates from solid to gas as the temperature rises, and forms a prefabricated crack structure inside the hot dry rock-like material. The shape, distribution and spatial characteristics of the cracks conform to the crack parameters previously designed by three-dimensional modeling, including aperture, aspect ratio and fractal dimension.

[0102] In addition, in order to realize the recovery and recycling of camphor, in the embodiment of the present application, a serpentine condenser is also connected to the gas outlet of the muffle furnace. The gaseous camphor is cooled in the condenser and condensed into solid camphor again, completing the recovery process. The condensing device can avoid the waste of camphor and reduce the emission of organic volatiles, providing support for the environmental protection of the experiment.

[0103] The preliminarily solidified hot dry rock-like material is placed in a muffle furnace, and the temperature of the muffle furnace is set to 200°C; camphor is converted from solid to gas by heating, and a prefabricated crack structure is formed inside the material. The spatial distribution of the cracks conforms to the crack model characteristics designed in the 3D modeling process; Through the heating and sublimation process of the embodiment of the present application, prefabricated cracks that meet the experimental requirements are finally formed inside the hot dry rock similar material, and the binder is completely solidified to enhance the overall performance of the material. The spatial distribution of the cracks is consistent with the real crack characteristics of hot dry rock, which provides a reliable experimental basis for studying the expansion law of hot dry rock cracks and fluid seepage characteristics. In addition, the recycling of camphor reduces costs and resource waste, and improves the economy and sustainability of the entire process.

[0104] S8, after the solidification and crack generation are completed, the hot dry rock-like material is taken out from the muffle furnace and cooled to room temperature to obtain a rock-like material with similar mineral composition and crack characteristics.

[0105] In the embodiment of the present application, the hot dry rock-like material that has been cured and cracked by heating in a muffle furnace is taken out and cooled to room temperature, and finally a rock-like material with prefabricated cracks inside and a microstructure similar to the prototype rock is obtained. The cooled material can be directly used for subsequent experimental research to further verify whether its various parameters meet the experimental requirements, and provide basic data support for the production of rock-like materials with different crack rates and characteristics.

[0106] Specifically, the parameters of the rock-like material after cooling can be measured, including the particle size distribution and volume fraction of minerals, the volume fraction of pores and fissures, pore diameter, aspect ratio and fractal dimension, to verify whether it is consistent with the three-dimensional scanning data of the prototype rock sample. If deviations are found, they can be optimized by adjusting the production process and proportion. In addition, after the material measurement is completed, the parameter information used in each production process can also be recorded, including the grading ratio of mineral particles, the amount of binder, the design parameters of the fracture model, the heating rate, the constant temperature time, etc. These production parameters are correlated with the final material properties to clarify the influence of different components and processes on the material properties. By optimizing and adjusting the proportions of different components and the process flow, orthogonal experiments are carried out, and the test results are recorded in the computer program to establish a production parameter database.

[0107] It should be noted that the database established by the embodiment of the present application can realize the automatic generation of rock-like material ratios and processes for different experimental needs. According to the CT scanning data of the prototype rock sample input into the database, the system can automatically generate a rock-like material ratio scheme and process flow that meets the specified rock characteristics. At the same time, the database can be applied to different types of rocks. It only needs to adjust the temperature and sublimation time of the muffle furnace, or use consumables with lower sublimation conditions instead of camphor, to produce rock-like materials that meet different experimental needs.

[0108] The embodiment of the present application forms a fast, efficient and scalable method for producing rock materials containing prefabricated fractures by systematically recording and database management of the production process. The method is highly similar to the prototype rock sample at the microscopic scale, and is suitable for the production needs of hot dry rock and other rock materials containing prefabricated fractures. It provides a reliable experimental basis for the study of fracture expansion laws, seepage characteristics, etc., and significantly improves the production efficiency and process standardization.

[0109] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this application can be executed in parallel, sequentially or in different orders, as long as the expected results of the technical solution of this application can be achieved, and this document is not limited here.

[0110] The above specific implementations do not constitute a limitation on the protection scope of this application. It should be understood by those skilled in the art that various modifications, combinations, sub-combinations and substitutions can be made according to design requirements and other factors. Any modifications, equivalent substitutions and improvements made within the spirit and principles of this application should be included in the protection scope of this application.

Claims

1. A method for producing rock-like materials with prefabricated cracks, characterized in that: The following steps are involved: The rock sample is placed in a dual-source dual-energy CT scanning system for scanning to obtain three-dimensional scanning data of the rock sample; Performing three-dimensional reconstruction and analysis on the three-dimensional scanning data to obtain the particle size distribution range and volume fraction of the minerals inside the rock, as well as the volume fraction, pore diameter, aspect ratio and fractal dimension of pores and cracks; Prepare mineral particles consistent with the mineral type inside the rock, crush the mineral particles of the same type into different particle size ranges according to the particle size distribution range and proportion of different minerals inside the rock, and calculate their stacking porosity after mixing; According to the stacking porosity of the mixed mineral particles, a high temperature resistant epoxy phenolic resin is calculated and added as a binder to form a uniform mixed material; The 3D printing technology was used to establish a fracture structure model that conforms to the real fracture structure distribution characteristics of hot dry rock, and camphor was selected as the consumable material for 3D printing fracture structure; The fracture structure model and the mixed material are placed in a container with a Teflon coating and stirred to mix evenly, the stirred materials are loaded into a mold, filled in layers and compacted, and the pressure is maintained until the material is initially solidified to generate a dry hot rock-like material; The dry hot rock-like material is placed in a muffle furnace, and the epoxy phenolic resin is accelerated to solidify by heating, and the camphor is sublimated to form a crack structure; After the solidification and crack generation are completed, the hot dry rock-like material is taken out from the muffle furnace and cooled to room temperature to obtain a rock-like material with similar mineral composition and crack characteristics.

2. The method according to claim 1, characterized in that Placing the rock sample in a dual-source dual-energy CT scanning system for scanning to obtain three-dimensional scanning data of the rock sample includes: The rock sample is placed in a dual-source dual-energy CT scanning system, wherein the system uses two X-ray sources with different energies to scan the rock sample, and the attenuation characteristics of different minerals in the rock under different energy X-rays are calculated by the following formula: in, and is the intensity of X-rays after penetrating the rock sample, and is the incident X-ray intensity of two different energy sources, and is the linear attenuation coefficient of the material under different energy rays, is the rock thickness; By taking the logarithm of the above formula and solving it in parallel, the linear attenuation coefficient of the mineral is obtained. According to the attenuation characteristics of the mineral, the type and density distribution of the mineral in the rock are determined.

3. The method according to claim 2, characterized in that The three-dimensional reconstruction and analysis of the three-dimensional scanning data to obtain the particle size distribution range and volume fraction of the minerals inside the rock, as well as the volume fraction, pore diameter, aspect ratio and fractal dimension of pores and cracks, includes: Reconstruct the three-dimensional scan data using three-dimensional reconstruction software, convert the three-dimensional scan data into a 16-bit grayscale image, and use a threshold segmentation method to obtain the spatial distribution characteristics of minerals inside the rock and the distribution characteristics of natural pores and cracks; Through the software annotation and analysis function, the particle size distribution range and volume fraction of minerals inside the rock are statistically analyzed, and the aperture, aspect ratio and volume fraction of the cracks are analyzed. At the same time, the fractal dimension function is used to calculate the fractal dimension of the cracks.

4. The method according to claim 3, characterized in that The step of preparing mineral particles of the same type as the minerals inside the rock, crushing the mineral particles of the same type into different particle size ranges according to the particle size distribution ranges and proportions of different minerals inside the rock, and calculating the stacking porosity after mixing, comprises: Based on the particle size distribution range and proportion of different minerals in the rock, a crusher is used to crush the mineral particles to reach the required particle size range; According to the particle sizes and volume fractions of different minerals in the rock, crushed mineral particles of different particle size ranges are mixed in proportion; The mixed mineral particles are filled into the mold in layers, compacted using a small vibrator and pressurized step by step to the target pressure, and the volume of the compacted particles is recorded; The stacking porosity is determined by calculating the ratio of the volume of the mixed particles to the total volume after compaction. The calculation formula for the stacking porosity is: in, is the stacking porosity, is the volume of mineral particles, is the pore volume between particles.

5. The method according to claim 4, characterized in that The method of calculating and adding high temperature resistant epoxy phenolic resin as a binder according to the stacking porosity of the mixed mineral particles to form a uniform mixed material comprises: The volume fraction of the pores between the particles is calculated by the stacking porosity, and the amount of the required binder is determined according to the density of the epoxy phenolic resin and the volume fraction of the mineral particles; The calculated epoxy phenolic resin is uniformly added to the mixed mineral particles, and it is ensured that it fully fills the pores between the particles to form a uniform mixed material.

6. The method according to claim 5, characterized in that The method of using 3D printing technology to establish a fracture structure model that conforms to the real fracture structure distribution characteristics of hot dry rock, and selecting camphor as a consumable material for 3D printing fracture structure, includes: A fracture structure model similar to the rock sample is established by computer modeling software. The model includes aperture, slenderness ratio and fractal dimension parameters. The total volume of the model is determined according to the volume fraction of the rock fractures. The formula is: in, is the total volume of the fracture structure model, is the volume fraction of rock pores, is the total volume of rock-like material; The fracture structure model is exported as a mesh file in .stl format, and the model is printed using a 3D printing device using camphor as a consumable.

7. The method according to claim 6, characterized in that The fracture structure model and the mixed material are placed in a container with a Teflon coating and stirred to mix evenly, the stirred materials are loaded into a mold, filled in layers and compacted, and the pressure is maintained until the material is initially solidified to generate a dry hot rock-like material, including: Placing the fracture structure model and the mixed mineral particle material together in a container with a Teflon coating on the inner wall, and mixing them by mechanical stirring or manual stirring to ensure that the fracture structure model, the mineral particles and the binder are fully and evenly distributed; The stirred mixed material is loaded into the mold in layers, and each layer of material is compacted using a vibrator to eliminate voids; A small pressure device is selected to pressurize the loaded material step by step. The target pressure is maintained for a period of time during the step-by-step pressurization process to ensure that the material is initially solidified and forms a dense structure. The pressure device is then removed and the mold is dismantled to generate a preliminarily solidified hot dry rock-like material.

8. The method according to claim 7, characterized in that The method of placing the hot dry rock-like material in a muffle furnace, accelerating the curing of the epoxy phenolic resin by heating, and causing the camphor to sublime to form a crack structure comprises: The preliminarily solidified hot dry rock-like material is placed in a muffle furnace, and the temperature of the muffle furnace is set to 200° C.; camphor is converted from a solid state to a gaseous state by heating, and a prefabricated crack structure is formed inside the material, and the spatial distribution of the cracks conforms to the crack model characteristics designed in the three-dimensional modeling process; A serpentine condenser is connected to the gas outlet of the muffle furnace, and the gaseous camphor is re-condensed into a solid through a cooling device, thereby realizing the recovery and reuse of the camphor.

9. The method according to claim 8, characterized in that Also includes: Measuring parameters of the rock-like material after cooling, including particle size distribution and volume fraction of minerals, volume fraction of pores and fissures, pore diameter, aspect ratio and fractal dimension, to verify whether it is consistent with the three-dimensional scanning data of the prototype rock sample; Record the manufacturing parameters used in each manufacturing process, including mineral particle grading ratio, binder dosage, fracture model design parameters, heating rate and constant temperature time; By analyzing the relationship between the production parameters and the final material properties, adjusting the ratio of different components and the production process, conducting orthogonal tests, and recording the test results in a computer program, a production parameter database is formed; Based on the production parameter database, the corresponding rock-like material ratio and process flow that meet the requirements of different rock characteristics are automatically generated according to the CT scanning parameters of the prototype rock sample.

Citation Information

Patent Citations

  • Manufacturing method of artificial rock crack rock sample

    CN107167349A

  • Artificial core and preparation method thereof

    CN108414312A

  • Method for preparing rock test-piece with non-filling internal defects

    CN111089772A

  • Rock-like similar material and preparation method thereof

    CN112358239A

  • Rock-like similar material and preparation method thereof

    CN112480601A

Cited By

  • Method for detecting porosity of in-situ dump-leached ore

    CN120558815A

  • Particle crushing strength prediction method and system considering pore parameters

    CN120877964A